1988
DOI: 10.1159/000120397
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Physiologic Monitoring of Pediatric Head Trauma Patients with Elevated Intracranial Pressure

Abstract: The management of pediatric patients with severe head trauma often requires aggressive physiologic monitoring and treatment. As intracranial pressure (ICP) increases, so does mortality. Yet attempts to decrease elevated ICP can cause physiologic and hemodynamic problems. In this retrospective analysis of 25 patients treated with ICP monitoring alone, ICP measurements plus mannitol, or ICP measurements plus pentobarbital (PB) induced coma/mannitol, survival rates were higher than predicted, particularly among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 32 publications
0
38
0
1
Order By: Relevance
“…Perhaps, our patients were able to be weaned from barbiturates earlier because they responded to lumbar drainage with lowered ICP while enjoying some form of barbiturate cerebral protection before institution of drain age. Given the potential deleterious effects of barbiturates, including cardiovascular depression, hypotension, sepsis, and dehydration [9], a safer alternative therapy for uncon trollable ICP is appealing. This report contributes to the literature another series of children with uncontrollable ICP, some of whom not only survived but actually had a functional outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, our patients were able to be weaned from barbiturates earlier because they responded to lumbar drainage with lowered ICP while enjoying some form of barbiturate cerebral protection before institution of drain age. Given the potential deleterious effects of barbiturates, including cardiovascular depression, hypotension, sepsis, and dehydration [9], a safer alternative therapy for uncon trollable ICP is appealing. This report contributes to the literature another series of children with uncontrollable ICP, some of whom not only survived but actually had a functional outcome.…”
Section: Resultsmentioning
confidence: 99%
“…5 The significance of intracranial hypertension in predicting outcome from TBI has been well studied since the 1960s. 2,4,12,17,19,20 Aside from its prognostic value, ICP monitoring also guides early diagnosis and management of intracranial hypertension. 29 Furthermore, there are now several evidence-based studies showing that ICP monitoring, when used in a protocol-based manner in neurosurgical ICUs, leads to improved outcomes in adjusted mortality rates for patients with severe TBI.…”
mentioning
confidence: 99%
“…In 1979, Marshall et al [14] reported on a series of 25 patients with ICP >40 mm Hg showing a reduction in mortality with the use of barbiturates. In 1988, Kasoff et al [15] reported on 25 TBI children who were treated with barbiturates with ICP, MAP, CPP, and hemodynamic stability monitoring. The authors showed an overall decrease in ICP and stressed the importance of hemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%